The Prognostic Role of Ribosomal Protein S6 Kinase 1 Pathway in Patients With Solid Tumors: A Meta-Analysis - Zhang, Shuo; Hu, Binwu; Lv, Xiao; Chen, Songfeng; Liu, Weijian; Shao, Zengwu (Frontiers in Oncology, 2019)
Abstract Background: Recent studies supported the predictive role of ribosomal protein S6 kinase 1 (S6K1), phosphorylated S6K1 (p-S6K1) and phosphorylated ribosomal protein S6 (p-S6) for the outcome of cancer patients. However, inconsistent results were acquired across different researches. To comprehensively and quantitatively elucidate their prognostic significance in solid malignancies, the current meta-analysis was carried out utilizing the results of clinical studies. Methods: We conducted the literature retrieval by searching PubMed, Web of Science, EMBASE, and Cochrane library to identify eligible publications. Data were collected from included articles to calculate pooled overall survival (OS), disease-free survival (DFS), recurrence-free survival (RFS) and progression-free survival (PFS). Hazard ratios (HRs) with 95% confidence intervals (CIs) served as appropriate parameters to assess prognostic significance. Results: Forty-four original studies were included, of which 7 studies were analyzed for S6K1, 24 for p-S6K1, and 16 for p-S6. The overexpression of p-S6K1 was significantly associated with poorer prognosis of solid tumor patients in OS (HR=1.706, 95%CI: 1.369-2.125, p<0.001), DFS (HR=1.665, 95%CI: 1.002-2.768, p=0.049). However, prognostic role of p-S6K1 in RFS and PFS was not found. The result also revealed that S6K1 and p-S6 were significantly associated with reduced OS (HR=1.691, 95%CI: 1.306-2.189, p<0.001; HR=2.019, 95%CI: 1.775-2.296, p<0.001, respectively). Conclusions: The present meta-analysis demonstrated that elevated expression of S6K1, p-S6K1 or p-S6 might indicate worse prognosis of patients with solid tumors, and supported a promising clinical test to predict solid tumor prognosis based on the level of S6K1 pathway.